Canagliflozin Prevents Lipid Accumulation, Mitochondrial Dysfunction, and Gut Microbiota Dysbiosis in Mice With Diabetic Cardiovascular Disease - Wang, Xueliang; Wang, Zhe; Liu, Di; Jiang, Hao; Cai, Chao; Li, Guoyun; Yu, Guangli (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is associated with cardiovascular disease (CVD) and sodium glucose cotransporter 2 inhibitors, as oral medications for T2DM treatment, have shown the potential to improve vascular dysfunction. The aim of this study was to evaluate the ability of canagliflozin (Cana) on relieving CVD in T2DM mice and its possible action mechanism. Mice with diabetic CVD was conducted by a high-fat diet for 24 weeks, followed by oral gavaging with metfotmin (200 mg/kg/d) or Cana (50 mg/kg/d) for six weeks. The result demonstrated that Cana reduced the serum lipid accumulation, and decreased arteriosclerosis index and atherogenic index of plasma. In addition, Cana treatment reduced the circulating markers of inflammation. More importantly, Cana improved cardiac mitochondrial homeostasis, and relieved oxidative stress. Moreover, Cana treatment alleviated the myocardial injury with decreasing levels of serous soluble cluster of differentiation 40 ligand and cardiac troponin I. Thus, cardiovascular abnormality was relieved by suppressing ﬁbrosis and basement membrane thickening, while elevating the cluster of differentiation 31 expression level. Importantly, Cana increased the ratio of gut bacteria Firmicutes/Bacteroidetes and the relative abundance of Alistipes, Olsenella and Alloprevotella, while decreased the abundance of Mucispirillum, Helicobacter and Proteobacteria, at various taxonomic levels in mice with diabetic CVD. In short, Cana treatment altered the colonic microbiota composition close to the normal level, which were related with the blood lipid, inflammation and oxidative stress, and might play a vital role in CVD. In general, the improvements of gut microbiota and myocardial mitochondrial homeostasis, may represent the mechanism of Cana on CVD treatment.